Teaching of decimal positional number system and decimal fractions in the 5-th grade - Bakštys, Albertas; Šukienė, Irena; Viliminė, Albina (Lietuvos matematikos rinkinys, 2002)
Long, almost 3500 years delay was observed, until the notion of positional number system originating from Babylon was introduced in Western Europe and, afterwards, in aIl over the modern world. This proves that acquaintance with such a complex concept as decimal fraction is must be started long before the arithmetic of decimal fractions is introduced. Teachers working experience using A. Bakštys and G. Bakštys textbook [5] in the 5-th grade is described in this paper.